2016
DOI: 10.1007/s10461-015-1278-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV Serostatus Disclosure to Sexual Partners Among Sexually Active People Living with HIV in South Africa: Results from the 2012 National Population-Based Household Survey

Abstract: This paper explores the prevalence and correlates of HIV seropositive status disclosure to sexual partners by people living with HIV (PLHIV) in South Africa. Secondary analysis of the 2012 South African National HIV Prevalence, Incidence and Behaviour Survey was conducted on data obtained from 934 sexually active PLHIV aged 15 years and older who responded to the question about HIV seropositive status disclosure. Overall, a large majority of respondents (77.1 %) reported disclosing their HIV-positive status to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
2
8
1
Order By: Relevance
“…However, this may be because participants who had not disclosed were not in a stable or committed relationship, as all participants in this study reported being sexually active. This is consistent with findings from the 2012 South African National HIV Prevalence, Incidence and Behaviour survey, where the analysis showed that those who were not married, including those living in common-law relationships, were 60% less likely to disclose their HIV-positive status when compared to those who were married [27,28].…”
Section: Discussionsupporting
confidence: 87%
“…However, this may be because participants who had not disclosed were not in a stable or committed relationship, as all participants in this study reported being sexually active. This is consistent with findings from the 2012 South African National HIV Prevalence, Incidence and Behaviour survey, where the analysis showed that those who were not married, including those living in common-law relationships, were 60% less likely to disclose their HIV-positive status when compared to those who were married [27,28].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, similar to the RapIT study results, a higher proportion of men was diagnosed with HIV and initiated ART, suggesting that the offer of immediate ART may be more attractive to men than women [14]. Being in a partnership may signify access to social support in some cases, but being in an insecure partnership may amplify fears associated with HIV status disclosure, and limit ART adherence [38‐44]. Fears of HIV stigma also compel some patients to access HIV care further away to avoid being identified at a nearby clinic [45].…”
Section: Discussionmentioning
confidence: 89%
“…In one telling illustration of this, businesses with known HIV-positive workers were shown to lose up to half of their customers out of fear of transmission and disdain for people living with HIV (Chao et al 2017). Stigma also represents a significant barrier to testing and makes people reluctant to disclose their serostatus to partners (Simbayi et al 2017;Treves-Kagan et al 2017). Contemplating this topic, Rosa explained that people are afraid of HIV, and that when someone is infected, it is not spoken of and then becomes a secret to the extent that no one can know, 'not even your own family' (field notes).…”
Section: Sociocultural Estrangement and Stigmamentioning
confidence: 99%